Transient Teachers: Mixed Messages of Schooling in Regional Australia - Carmen Mills; Trevor Gale (Journal of Research in Rural Education, 2003)
This article explores the transience and mobility of teachers working in an isolated community: a secondary school in regional Australia. Drawing on parent, student, and teacher interviews, we ask: how should we understand these teacher commitments to schooling and how does this influence parents' and students' commitments and understandings of the "outside" value of their community? Responses to these questions are theorized utilizing the social theory of Pierre Bourdieu. Drawing on this work we argue that, even though teachers in this context are the bearers of highly prized capitals, they act more as gatekeepers than as their distributors and/or challengers. While we conclude that teachers may need to address their mobility and the messages this conveys in order to make a difference in such schools and communities, we also acknowledge that there are complexities related to staff residing in the community given its treatment of outsiders.